Engaging Neural Plasticity in Senior High School Students: The Impact of Guided Discovery Teaching Method on Achievement in Circle Theorems - Nurideen, Suraj; Amenyi, Churcher Kwesi; Wilmot , Dennis; Susuoroka, Gabina (American Journal of Education and Practice, 2024)
Purpose: The study's objective was to ascertain how circle theorem achievement in SHS students was affected by the guided discovery teaching method, a student-centered approach associated with improved neural plasticity. Materials and Methods: Two Form 2 classes from various Wa Municipal schools were chosen for the study using convenient, purposeful, and straightforward random sampling techniques. The study adopted a non-equivalent quasi-experimental design to compare students who are taught with the guided discovery method and the traditional method of teaching circle theorems concepts. The sample size was composed of 164 students. Using a separate t-test and descriptive statistics, the Geometry Achievement test was investigated. A pre-test was given before the experiment (post-test) began. The students who engaged in guided discovery instruction outperformed than those who did not when teaching and learning Circle theorems. Findings: The findings suggested that student-centered methods like guided discovery can greatly improve students' achievement in the study of circle theorems. One of the implications derived from the study indicated that guided discovery teaching approach offers students the chance to put a method of learning into practice after they have used it. This was done by using illustrations of diagrams on cardboard. This must be considered in the planning of educators and subject-matter experts. For pre-tertiary education, the government must make it mandatory to use cardboard, mathematical instruments, and instructional sheets as teaching aids. Since visual representations of Euclidean Geometry diagrams bring reality to teaching and learning through pictures and diagrams, the importance of visualization and experimentation in learning circle theorems should not be underestimated by teachers or students. This will improve their conceptual understanding. Implications to Theory, Practice and Policy: One can recommend that in order to enhance the performance of SHS students, it will be most advantageous to introduce guided discovery teaching methods to pre- and in-service teachers, through promotion by Ghana Education Service and/or other stakeholders in the education sector. This introduction may be distributed through workshops and seminars for mathematics teachers' instructional techniques and skills will improve as a result. This study has added a lot to our understanding of the world. The guided discovery teaching method approach to teaching circle theorems has been strengthened and expanded as a result of this research, first and foremost. This thesis thus makes a substantial enhancement of the body of knowledge. The research also explains and backs up the notion that guided discovery methods aid students' academic endeavors. This shows that the teaching process engages students' attention and improves their capacity for memory and recall.